A Low-Profile Dual-Band Directional Antenna for Unmanned Aerial Vehicle Applications. (17th October 2022) - Jin, Hui; Han, Chong-Zhi; Fu, Yanzhi; Yang, Huaiwen
Abstract : A low-profile dual-band directional antenna operating at both 2.4 and 5 GHz for wireless local area networks (WLANs) for unmanned aerial vehicles (UAVs) applications is proposed in the paper. Two pairs of dipole antenna arrays with different electrical lengths are utilized to achieve dual-band directional radiation performance, which is desirable for a remote-control unit of the UAVs. Note that the directional radiation characteristic is obtained according to the double-dipole antennas driven by antiphase signals (W8JK), provided the distances between different dipole antennas are properly optimized. Note that the distance between the two longer dipoles, as well as the two shorter dipoles, can be calculated by equations. For each pair of dipoles with equal electrical lengths, an antiphase along the two dipoles can be obtained, and directional radiation characteristics can be achieved in the dual band. Coplanar strips (CPS) are employed as feeding networks, which lie on the same substrate layer as the antenna arrays, resulting in a low profile of merely 0.762 mm. Also, the overall size of the antenna together with the feeding network is 58.42 × 32.58 × 0.762 mm 3 . To verify the performance of the proposed antenna, a prototype is fabricated and measured. The measured gain is 5.2 and 7.0 dBi, respectively, in the 2.4 and 5.8 GHz bands. The measured reflection coefficients as well as radiation patterns are consistent with those of the simulated results. The proposed antenna scheme can be a good candidate for UAV applications with the advantages of a lower profile, dual-band characteristics, directional radiation characteristics, and a simple assembly. Since the remote-control unit operates at 2.4 GHz and 5.8 GHz to control the UAV unit, the low-profile dual-band directional radiation antenna has extensive application prospects when integrated into the space-limited unit.